GOVERNMENT AND PESANTREN COPING WITH TERRORISM ISSUE IN MALANG: A Collaboration Model - Yumitro, Gonda; Kurniawati, Dyah Estu (UIN Sumatera Utara, 2020)
Abstract: This article discusses the collaboration model between the government and pesantren in dealing with the issue of terrorism in Indonesia. This topic is important because terrorism has become a complex issue, and the solution requires good collaboration from all groups, both government and non-government. Therefore, the authors conducted qualitative research using in-depth interviews, literature reviews, and Focus Group Discussions (FGD) as data collection methods. The informants and participants were the representatives of the government officers and the leaders of pesantren with various backgrounds. The data collected were analyzed using Nvivo 12 plus. The authors found that the government and pesantren had collaborated to face the issue of terrorism, but these efforts were not optimal because there were still several challenges. Thus, it is necessary to develop a model of job sharing to develop the preceding collaboration. Keywords: model, collaboration, government, pesantren, terrorism, Indonesia